Bronchial artery embolization leading to acute myocardial infarction: a case report on bronchial artery-coronary artery fistula - Shougang Sun; Qi Zou; Peng Chang (BMC Cardiovascular Disorders)
Abstract A 22-year-old woman presented with hemoptysis for three days, averaging 150 ml of blood per day. She had no history of childhood chest disease. On admission, a chest scan suggested a potential lung infection, and laboratory results showed no significant abnormalities. Despite continuous infusion of posterior pituitary hormone, her symptoms persisted. We performed bronchial arteriography and embolization using 150–350 μm microsphere particles. During the procedure, the patient developed chest pain. An electrocardiogram (ECG) showed abnormal Q-waves and ST-T elevation, with vital signs indicating hypotension and elevated myocardial enzymes suggesting acute myocardial infarction (AMI). Repeated arteriography revealed a bronchial artery-right coronary artery fistula, likely worsened by a dislodged gelatin sponge blocking coronary microvessels. The embolization was halted, and treatment with low molecular weight heparin and aspirin was initiated. By the fifth postoperative day, the patient’s ECG indicated an abnormal Q wave in the inferior leads, and myocardial enzymes were gradually returning to normal. One week later, coronary angiography revealed no blockage, and the patient was discharged after stabilization. The cardiovascular magnetic resonance (CMR) indicated myocardial necrosis and edema in the inferior wall of the heart. During subsequent follow-up, the patient reported no significant chest pain or recurrence of hemoptysis.